Anion Exchanger 2 Regulates Dectin-1-Dependent Phagocytosis and Killing of Candida albicans - Urso, Katia; Charles, Julia F.; Shull, Gary E.; Aliprantis, Antonios O.; Balestrieri, Barbara (PloS one, 2016)
Anion exchanger 2 (Ae2; gene symbol, Slc4a2) is a plasma membrane Cl-/HCO3- exchanger expressed in the gastrointestinal tract, kidney and bone. We have previously shown that Ae2 is required for the function of osteoclasts, bone resorbing cells of the macrophage lineage, to maintain homeostatic cytoplasmic pH and electroneutrality during acid secretion. Macrophages require endosomal acidification for pathogen killing during the process known as phagocytosis. Chloride is thought to be the principal ion responsible for maintaining electroneutrality during organelle acidification, but whether Cl-/HCO3- exchangers such as Ae2 contribute to macrophage function is not known. In this study we investigated the role of Ae2 in primary macrophages during phagocytosis. We find that Ae2 is expressed in macrophages where it regulates intracellular pH and the binding of Zymosan, a fungal cell wall derivative. Surprisingly, the transcription and surface expression of Dectin-1, the major phagocytic receptor for Candida albicans (C. albicans) and Zymosan, is reduced in the absence of Ae2. As a consequence, Zymosan-induced Tnfα expression is also impaired in Ae2-deficient macrophages. Similar to Ae2 deficiency, pharmacological alkalinization of lysosomal pH with bafilomycin A decreases both Dectin-1 mRNA and cell surface expression. Finally, Ae2-deficient macrophages demonstrate defective phagocytosis and killing of the human pathogenic fungus C. albicans. Our results strongly suggest that Ae2 is a critical factor in the innate response to C. albicans. This study represents an important contribution to a better understanding of how Dectin-1 expression and fungal clearance is regulated.